The Role of Digital Mindset and Professional Performance Management in Optimizing the Potential of Generation Z - Achmad Singgih Laksono; Siti Mujanah; Abdul Halik (AGUSPATI Research Institute, 2026)
This article aims to analyze the role of digital mindset and professionalism of human resource management in optimizing the potential of Generation Z to improve performance. This study uses a qualitative approach with a literature study method. Data were obtained from relevant books, scientific articles, and journals regarding digital mindset, human resources, performance management, and characteristics of Generation Z. The results of the study show that Generation Z has strong potential in technology adaptation, creativity, flexibility, and innovation, but also faces challenges in the form of digital distractions, low job security, and turnover tendencies. Therefore, HRM needs to implement professional performance management through planning, monitoring, development, assessment, and performance awards. This article emphasizes that the success of Generation Z's management does not only depend on technology, but on the ability of organizations to build a digital mindset and adaptive work systems.